Testing for the Presence of Asymmetric Information in the Oil Market: A VAR Approach - Troug, Haytem Ahmed; Sbia, Rashid (International Journal of Economics and Financial Issues, 2015)
This paper aims at providing empirical support to claims made by officials in oil-producing countries that investors in the New York Stock Exchange market are involved in the disruption of oil production in some OPEC countries. The claims state that some investors in the NYSE are financing militias in those countries to close down oilfields and ports, and buy oil before this incident occurs. By doing so, they have access to information that no one else in the market has, and make profits from this information. Using a VAR model approach to detect this phenomenon, and being inspired by the asymmetric information theory, we fail to support those claims. We tried to put this theory under investigation by running test on three oil-disruption incidents that occurred in 2013, and all of the results turned out to be insignificant. Nevertheless, this approach was able to detect a period which might involve asymmetric information in the NYSE. In addition, using a VAR model enabled us to measure the duration and magnitude of the effect of a shock in volumes of trade on oil prices in that market. Keywords: Asymmetry of Information; Stock Market; Oil Market; OPEC; NYSE. JEL Classifications: C50; C58; G02; G14